Mussel Inspired Highly Aligned Ti3C2Tx MXene Film with Synergistic Enhancement of Mechanical Strength and Ambient Stability - Lee, Gang San; Yun, Taeyeong; Kim, Hyerim; Kim, In Ho; Choi, Jungwoo; Lee, Sun Hwa; Lee, Ho Jin; Hwang, Ho Seong; Kim, Jin Goo; Kim, Dae-Won; Lee, Hyuck Mo; Koo, Chong Min; et al. (AMER CHEMICAL SOC, 2020)
Two-dimensional (2D) MXene has shown enormous potential in scientific fields, including energy storage and electromagnetic interference (EMI) shielding. Unfortunately, MXene-based material structures generally suffer from mechanical fragility and vulnerability to oxidation. Herein, mussel-inspired dopamine successfully addresses those weaknesses by improving interflake interaction and ordering in MXene assembled films. Dopamine undergoes in situ polymerization and binding at MXene flake surfaces by spontaneous interfacial charge transfer, yielding an ultrathin adhesive layer. Resultant nanocomposites with highly aligned tight layer structures achieve approximately seven times enhanced tensile strength with a simultaneous increase of elongation. Ambient stability of MXene films is also greatly improved by the effective screening of oxygen and moisture. Interestingly, angstrom thick polydopamine further promotes the innate high electrical conductivity and excellent EMI shielding properties of MXene films. This synergistic concurrent enhancement of physical properties proposes MXene/polydopamine hybrids as a general platform for MXene based reliable applications.
Keywords: SURFACE; POLYDOPAMINE; TRANSFORMATION; NANORIBBONS; CHEMISTRY; DOPAMINE; GRAPHENE